Research on Risk Assessment Technology of Investment Plan Implementation of Electricity Grid Construction Projects Based on Automatically Generated Fixed Asset Investment. Issue 4 (February 2020) - Zhou, Ming; Lu, Shengwei; Wu, Qiang; Jin, Sha; Yan, Jiong; Sang, Zixia; Fang, Rengcun
Abstract: In order to achieve accurate verification of the implementation of power grid infrastructure investment plan, support the dynamic monitoring and risk assessment of annual investment plan implementation. Based on the "three rates in one" Investment completion collection value of 110 kV and above grid infrastructure projects, this paper constructs a risk assessment model for the implementation of the investment plan of grid infrastructure projects. Evaluate the rationality of the current reported investment progress, predict the risk of the implementation of the investment plan and quantify the risk amount of the implementation of the plan, timely discover the risk of the implementation of the investment plan, promote the timely resolution of problems, and improve the investment lean management level of power grid enterprises.